GLOBAL CLIMATE CHANGE: CARBON CAPTURE TECHNOLOGIES AND THEIR ROLES IN THE MITIGATION OF CLIMATE CHANGE - Engr Theo Aku Ugah; Prof. Okeke Gerald Ndubuisi; Engr. Prof Sony Emeka Ali; Associate Professor Cynthia Amaka Obiorah Ph.D; Dr. Omatseyione Nesiama; Engr. Cletus Onyemhese Agbakhamen; Engr. Ogheneteme Pupu Okoro (IPHO-Journal of Advance Research in Science And Engineering, 2025)
The escalating rates of carbon dioxide (CO?) releases into the atmosphere due to industrial and anthropogenic activities need carbon capture technologies (CCTs) as critical partfor climate change mitigation. The elevated levels of CO? emissions into the biosphere have varying degrees of impacts on the climate of nations and biodiversity in general. These impacts include global warming, floods, greenhouse effect, acid rain, ozone layer depletion and other secondary effects on both aquatic and terrestrial natural habitats. There are increasing concernsabout the fast-depleting populations of animal speciesat various stages of existential threats or even extinction. This unfortunate trend, if not adequately addressed could affect the food-chain adversely exposing humanity to grave dangers and threatening longevity of homo sapiens. In our current highly technologized global environment, scientists and engineers are working assiduously on promoting green technologies and evolving projects aimed at preserving the ecological profiles of communities in such manners that the health of our ecosystems is adequately protected legally and technologically through the application of eco-friendly engineering practices. This paper examines one of these engineered solutions known as CCTs, their current state, technological mechanisms, challenges, and ways they could effectively be integrated into broader climate policies by nations to ensure environmental sustainability. This paper looks to illuminate the readers on the dangers of increasing CO? levels, their primary and secondary effects on the ecosystem and environmental sustainability. Despite past efforts directed at addressing environmental hazards by organs of the United Nations (UN) and non-governmental organizations (NGOs), the menace has not abated appreciably compared to the increasing threats to our ecological systems. It has become very necessary to develop technologies that could mitigate the effects of CO? releases into the biosphere and promote environmental sustainability for the benefits of both present and future generations, because life revolves around the environment for preservation.